Mobile Phone and Pakistani Youth: A Gender perspective - Zarqa Shaheen Ali (Journal of Telematics and Informatics, 2013)
This research was designed to open a window on youngsters’ use of mobile phone. The present study examined the purposes and patterns of usage of mobile phone use– in both male and female students of undergraduate and graduate level at seven public sector universities of the Province of Punjab (Pakistan). The study examined and reviewed the literature to understand the patterns and purposes of  mobile phone use from a global perspective in both developed and developing societies.  This provided in a context for the study of mobile phone use in the local Pakistani situation. The findings of the study conclude that gender differences exist in purposes and patterns of usage of mobile phone use, though they are not very significant. There is a change in the trend among females as the usage of the mobile phone is increasing. Contrary to the general perception about gender conscious Pakistani society, females are almost on par with males in using mobile phone. However, existing gender stereotypes maintain the status quo in terms of purposes of using mobile phone.